A probable cheating-free (t, n) threshold secret sharing scheme with enhanced blockchain. (May 2022) - Biswas, Anindya Kumar; Dasgupta, Mou; Ray, Sangram; Khan, Muhammad Khurram
Highlights: Cheating-free ( t, n ) threshold secret sharing scheme (SS) with a consensus mechanism using Blockchain based SS scheme is presented. Dealer acts as a miner and builds a 2-block length Blockchain per session with dealer's identity and public parameters in genesis-block, and participants' share in the remaining block secretly. Participants verify received shares with Blockchain copy, and reconstruct polynomial and get secret if verification is successful. Security analysis and comparison with others as performance analysis are provided. Abstract: A cheating-free ( t, n ) threshold secret sharing scheme using Blockchain is presented, where Shamir's technique is followed and the Blockchain vulnerabilities due to PoW/PoS (Proof-of-Work/Stake) consensus, are removed. We address the shares' cheating issues and design a Blockchain based SS scheme, in which the participants' shares are recorded secretly in a block and the dealer's identity along with other parameters are made visible through the genesis block. Our scheme uses a short-length Blockchain comprising 2 blocks per secret negotiation session. The main objectives are to improve Shamir's secret sharing scheme with Blockchain such that the cheating activities from dealer and/or participants become infeasible, and to enhance Blockchain technology with a consensus mechanism using Blockchain based SS scheme such that insecurity of PoW/PoS consensus are avoidable. The security and performance analysis of the scheme are provided. Although Blockchain increases some overheads, it makes a complete cheating-free SS scheme. Graphical abstract: Image, graphical abstract